Parents supporting learning: a non-intensive intervention supporting literacy and numeracy in the home learning environment. Issue 2 (2nd April 2016) - Niklas, Frank; Cohrssen, Caroline; Tayler, Collette
ABSTRACT: In Australia, emphasis in early childhood education policy is placed on the importance of the role of the family as a child's first educator, and finding effective ways to raise the effectiveness of parents in supporting children's learning, development and well-being. International studies demonstrate that the home learning environment (HLE) provided by parents is closely associated with children's cognitive outcomes: literacy activities at home are likely to predict children's literacy abilities and numeracy activities at home are likely to predict children's numeracy abilities. However, studies focusing on building the capacity of primary caregivers to increase informal learning opportunities, such as enhancing children's literacy and numeracy learning in the HLE, have rarely been the focus of research. This study uses a sample of 113 four-year-old children to explore the association of specific aspects of the HLE with different child outcomes while controlling for child and family characteristics. In addition, a non-intensive, yet purposeful and systematic intervention to draw parents' attention to the principles of dialogic reading and the principles of counting was introduced. Study findings suggest that parents responded positively to this approach, and that literacy and numeracy aspects of the HLE were specific predictors for children's numeracy and literacy competencies.